Pengaruh Penerapan LKS Berbasis Strategi Pembelajaran Peningkatan Kemampuan Berpikir (SPPKB) terhadap Keterampilan Berpikir Kreatif Siswa Kelas XI SMAN 1 Solok Selatan - Wike Indriani (PILLAR OF PHYSICS EDUCATION, 2014)
Learning outcomes of Physics are not optimal shows that students do not understand the concepts of physics in comprehensif and detail, this means creative thinking skills of students is still low. One contributing factor is the lack of effective learning strategies and worksheets used by teachers in the learning process both in the lab and non lab activities. Learning strategiesincreased abilityto think equipped with worksheet based learning strategiesincreased abilityto thinkis the expected effective way to improve students' creative thinking skills. Therefore, researchers compiled Physics worksheets using the stages of learning strategiesincreased abilityto think. This study aimed to examine the effect of the use of worksheets based learning strategiesincreased abilityto think the creative thinking skills of student XI science SMAN 1 Solok Selatan.Type of research is quasi-experimental with a Randomized Control Group Only Design. The population of this research is class XI Science SMAN 1 Solok selatan listed on the academic year 2013/2014. Sampling was done by purposive sampling technique. The instrument used in this study is the final test for cognitive learning outcomes (creative thinking skills). The results showed that the working hypothesis which states that "there is a significant influence use of worksheets Strategi pembelajaran peningkatan kemampuan berpikir (SPPKB)to the creative thinking skills of students of class XI Science SMAN 1 Solok Selatan" can be accepted on accurate level 95 %. Thus, the use of worksheets based Strategi pembelajaran peningkatan kemampuan berpikir (SPPKB)can enhance creative thinking skills of students